Pendampingan Laporan keuangan Bagi Kelompok Usaha Budidaya Ikan Air Tawar Desa Pematang Rambai : Assistance with financial reports for Pematang Village Freshwater Fish Cultivation Business Group Rambai - Mahary, Azizah; Suriono, Hadi; Rahman, Abdul (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Freshwater fish cultivation is a promising business prospect to be developed in Batu Bara Regency. One of the cultivator groups that is active in fish production is "Subur Makmur" which is located in Pematang Rambai Village. Financial reports are basically the result of reflection of the many transactions that occur in a company. Business development can be hampered if the owner does not understand financial reports. This is the problem faced by the group, namely that it has not implemented financial reports properly so that the group does not know clearly the profits or losses obtained. This service activity aims to provide knowledge and business financial management skills to groups of freshwater fish farmers. The implementation method is carried out by counseling and mentoring. The results achieved from this activity are that the cultivator group has become skilled at analyzing fish production costs and is able to prepare financial reports.